Comparison of various atomic compositions of Au@Pd/C, Pd/C, and AuPd/C electrocatalysts for direct ethanol fuel cells. Issue 3 (20th February 2020) - Fontes, Eric H.; Nandenha, Júlio; Piasentin, Ricardo M.; De Souza, Rodrigo F. B.; Neto, Almir O.
Abstract: Pd/C, Au@Pd/C (core‐shell), and AuPd/C (AR—consisting in Au microparticles) were used as electrocatalysts for ethanol oxidation in alkaline medium. A synergistic effect between Au and Pd atoms in Au@Pd/C makes the binding between ethanol and Au@Pd/C stronger. This leads to product formation in higher potentials and can be useful to select ethanol products. We also showed that the atomic composition of the electrocatalysts to be used in fuel cells and in powder form to be used in electrochemical experiments are very similar, reaching high values of correlation. The depth profiling X‐ray photoelectron spectroscopy for the anode catalysts to be used in fuel cells can provide new insights about ethanol oxidation in direct ethanol fuel cells (DEFCs), for instance, metal oxide species can act in fuel cells environment. In terms of electric generation, Au@Pd/C presented a better performance in electrochemical experiments; the current density was about 1.6 times higher than the peak current density obtained for Pd/C. In terms of electrochemical stability, Au@Pd/C presented better final current density when compared to Pd/C and AuPd/C electrocatalysts. However, in DEFC experiments, Pd/C showed better performance.